2017
DOI: 10.1080/10409238.2017.1337705
|View full text |Cite
|
Sign up to set email alerts
|

Lytic transglycosylases: concinnity in concision of the bacterial cell wall

Abstract: The lytic transglycosylases (LTs) are bacterial enzymes that catalyze the non-hydrolytic cleavage of the peptidoglycan structures of the bacterial cell wall. They are not catalysts of glycan synthesis as might be surmised from their name. Notwithstanding the seemingly mundane reaction catalyzed by the LTs, their lytic reactions serve bacteria for a series of astonishingly diverse purposes. These purposes include cell-wall synthesis, remodeling, and degradation; for the detection of cell-wall-acting antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
188
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(203 citation statements)
references
References 300 publications
10
188
0
Order By: Relevance
“…Addition of 0.2% glucose could not phenotypically suppress MltE complementation of the ∆2 LTG mutant chaining defect (data not shown), suggesting that perhaps leaky expression from P tac (Rosano and Ceccarelli, ) is sufficient for supporting cell separation. MltE has a relatively broad spectrum of PG substrate specificity, shown in vitro to generate products indicative of both endo‐ and exolytic cleavage on denuded or un‐crosslinked muropeptides (Lee et al , ; Dik et al , ; Byun et al , ), and has no known homolog in V. cholerae. Overexpression of mltE was not toxic in a WT background, suggesting that it primarily digests septal PG in the V. cholerae ∆2 LTG mutant (Fig. )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of 0.2% glucose could not phenotypically suppress MltE complementation of the ∆2 LTG mutant chaining defect (data not shown), suggesting that perhaps leaky expression from P tac (Rosano and Ceccarelli, ) is sufficient for supporting cell separation. MltE has a relatively broad spectrum of PG substrate specificity, shown in vitro to generate products indicative of both endo‐ and exolytic cleavage on denuded or un‐crosslinked muropeptides (Lee et al , ; Dik et al , ; Byun et al , ), and has no known homolog in V. cholerae. Overexpression of mltE was not toxic in a WT background, suggesting that it primarily digests septal PG in the V. cholerae ∆2 LTG mutant (Fig. )…”
Section: Resultsmentioning
confidence: 99%
“…. MltE has a strong preference for uncrosslinked PG (Lee et al , ; Dik et al , ; Byun et al , ), providing a possible explanation for its lack of general toxicity, since the main body of the cell’s PG is generally crosslinked (Desmarais et al , ). Incidentally, this also suggests that septal PG in ∆2 LTG is largely uncrosslinked; which would be consistent with completed or concurrent amidase or endopeptidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…MltB, a member of the lytic transglycosylase (LT) family, cleaves the glycosidic bond between N-acetylmuramic acid (MurNAc) and N-acetylglucosamine (GlcNAc) residues of peptidoglycan (PG), concommittantly forming a 1,6-anhydro bond in the MurNAc residue (Dik et al, 2017;Höltje et al, 1975;Scheurwater et al, 2008). These enzymes are involved in remodeling of the PG layer and releasing PG fragments (1,6-anhydro-muropeptides), and consequently, important for cell wall integrity (Dik et al, 2017). Recently, it was shown that LTs are important for pathogenesis in Neisseria gonorrhoeae, Brucella abortus and Edwardsiella tarda (Bao et al, 2017;Knilans et al, 2017;Liu et al, 2012;Ragland et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The breadth of study of this β‐lactamase‐resistance response—from the molecular (antibiotic structure) to the macromolecular (protein‐ligand interaction, biochemical pathways) to the microbiological and the clinical—requires the medium of the comprehensive review . Here, we focus on the involvement of a family of important enzymes—the lytic transglycosylases—in peptidoglycan recycling and β‐lactamase induction …”
Section: Abetting the β‐Lactam Antibiotics Against Gram‐negative Bactmentioning
confidence: 99%
“…[221][222][223][224][225][226][227][228] Here, we focus on the involvement of a family of important enzymes-the lytic transglycosylases-in peptidoglycan recycling and β-lactamase induction. 229,230 The lytic transglycosylases (LTs) are periplasmic enzymes (many, but not all, lipoproteins) that catalyze the deconstruction (hence "lytic") of the polymeric peptidoglycan through the nonhydrolytic cleavage of the glycan strand of the peptidoglycan (hence, the awkward "transglycosylase"). Among the ensemble of cell-wall deconstructing enzymes that are found in the periplasm, 98,231,232 the lytic transglycosylases have a central position both with respect to key pathways and events.…”
Section: Abetting the β-Lactam Antibiotics Against Gram-negative Bamentioning
confidence: 99%